Enhancement of Lipid Metabolism and Hepatic Stability in Fat-Induced Obese Mice by Fermented Cucurbita moschata Extract. (13th March 2018) - Hossain, Md. Akil; Lee, Seung-Jin; Park, Na-Hye; Birhanu, Biruk Tesfaye; Mechesso, Abraham Fikru; Park, Ji-Yong; Park, Eun-Jin; Lee, Sam-Pin; Youn, Sun-Joo; Park, Seung-Chun
Abstract : The aim of this study was to evaluate the potentials of fermented Cucurbita moschata extract (FCME) in the treatment of obesity and nonalcoholic fatty liver disease (NAFLD). Five-week-old male C57BL/6 mice were assigned to 6 groups and treated for 8 weeks by feeding the normal diet (ND) and high fat diet (HFD) with and without FCME. Changes in body weight gain and consumption of feed and water were recorded. Major organs, adipose tissues, and blood samples were collected after the experimental period. The serum lipid profile, histological features of liver and adipose tissues, and mRNA expression of different adipogenic/lipogenic genes from liver tissue were evaluated. The supplementation of FCME in HFD significantly prevented HFD-induced increment of bodyweight. The adipose tissue mass, liver enzymes, and plasma lipids were also reduced significantly ( p < 0.05 ) by the consumption of FCME. The mRNA expressions of adipogenic/lipogenic genes (PPAR γ, C/EBP α, C/EBP β, C/EBP γ, and SREBP-1C) in FCME-treated obese mice were considerably ( p < 0.05 ) suppressed. FCME showed its antiobesity potential by suppressing the body weight gain and by modulating the plasma lipids and liver enzymes through the regulation of adipogenic/lipogenic transcriptional factors. Fermented Cucurbita moschata could be an opportunistic agent in controlling obesity and fatty liver changes.